Possible association between subclinical hypothyroidism and age at menopause in Colombian women - Álvaro Monterrosa-Castro; Angelica Monterrosa-Blanco; Sandra Sánchez-Zarza (Gynecological Endocrinology)
Objective To evaluate the association between subclinical hypothyroidism with early menopause, premature menopause, and last menstrual bleeding before the natural age of menopause.Methods This was a cross-sectional study conducted in 643 postmenopausal women aged 40–69 years. Groups were formed according to last menstrual episode: ≥45 [Natural age at menopause], 40–44 and [Early menopause], <40 [Premature menopause], and <45 [last menstrual episode before the natural age of menopause]. The Zulewski scale was applied to identify manifestations related to hypothyroidism and subclinical hypothyroidism, diagnosed with a serum TSH > 4.5 µIU/mL plus T4-free between 0.7 and 1.9 ng/dL.Results It was found that 24.4% had the last menstrual episode before the natural age of menopause, 18.6% had early menopause, and 5.7% had premature menopause. Subclinical hypothyroidism was diagnosed in 4.5% of patients. Among women with subclinical hypothyroidism, there was a higher frequency of early menopause, premature menopause, and last menstrual episode before the natural age of menopause, than in women without subclinical hypothyroidism (p < 0.05). Paresthesia (50%) and dry skin (40.7%) were the most reported hypothyroidism-related manifestations. Early menopause, premature menopause, and last menstrual episode before the natural age of menopause were associated with subclinical hypothyroidism, OR: 3.37 [95% CI: 1.40–8.10], OR: 4.31 [95% CI: 1.24–14.97], and OR: 3.57 [95% CI: 1.57–8.10], respectively.Conclusions The last menstrual episode before the natural age of menopause, early menopause, and premature menopause were significantly associated with a higher chance of subclinical hypothyroidism